Potensi Pangan Fungsional Tradisional Lombok: Tinjauan Literatur Gizi, Bioaktivitas, dan Peluang Pengembangan - Isnain, Fuad Sauqi; Apriyanditra, Wiwin; Afni, Nur (Politeknik Negeri FakFak, 2025)
Lombok Island is home to a rich culinary heritage, with traditional dishes deeply rooted in Sasak culture and potential functional food value. This literature review investigates five iconic Lombok dishes—Ayam Taliwang, Plecing Kangkung, Sate Bulayak, Ares, and Beberuk Terong—focusing on their nutritional profiles, bioactive compounds, and health-related properties. Adopting the PRISMA-ScR approach, this study synthesizes 30 scientific articles published between 2014–2024 and compares findings with the Indonesian Food Composition Table (TKPI). Results reveal the presence of bioactive compounds such as capsaicin, curcumin, allicin, flavonoids, and nasunin, with antioxidant, antidiabetic, immunomodulatory, and cardioprotective effects. The review highlights challenges in food safety (e.g., acrylamide, aflatoxin risks), along with the need for standardized recipes and modern packaging strategies. The paper recommends further scientific validation and sustainable innovation to transform Lombok's traditional cuisine into evidence-based functional food products that strengthen local identity, promote public health, and boost Indonesia’s healthy food industry.